Peculiarities of Creating a Musical Performance - Maryash Ismailova; Nurjanov Ruslanbek (Web of Journals Publishing, 2023)
The emergence of the genre of complex synthetic art with music is definitely connected with the rich artistic heritage of the Uzbek people and the talented people who can translate this heritage into the language of modern theater. This genre, which initially appeared in the form of small musical scenes, developed as a separate art direction in Uzbek theater with the creation of Ghulam Zafari's "Halima", Khurshid's "Farhad and Shirin", "Layli and Majnun". It should be noted that, in the past, this "folklore genre, transitory, only a bridge tool for the transition to opera art" was an obstacle to the path of musical drama, but it continued to develop. The regional theaters called "Musical Drama and Comedy Theater" aimed at staging both pure drama and musical drama works are based on the experiences of the current National Academic Drama Theater in the field of drama, the Republican Music Theater in the 1930s, and then the Music Theater named after Muqimi in the field of musical drama. He created artistic and aesthetic values that were added to the treasury of our nation.
Keywords: Musical drama, performance, theater, art, genre, drama, comedy, tragedy, dramatic genre, opera, ballet.